The first microcaddisflies Metrichia Ross, 1938 recorded in Tocantins State, northern Brazil (Trichoptera: Hydroptilidae): Metrichia elongata sp. nov. and Metrichia vulgaris Santos, Takiya & Nessimian 2016 - Carvalho, Bruna Laise Dos Santos; Moreno, Lucas; Desidério, Gleison Robson; Pes, Ana Maria; Hamada, Neusa (Zootaxa, 2024)
The microcaddisfly Neotropical genus Metrichia Ross, is recorded for the first time from the state of Tocantins, northern Brazil, through the discovery of two species: Metrichia elongata sp. nov. and Metrichia vulgaris Santos, Takiya & Nessimian 2016. Herein, the new species is described and illustrated based on males collected in a protected and preserved area in Cerrado biome of Tocantins. Metrichia elongata sp. nov. can be recognized mainly by the type and position of setae on the inferior appendages and morphology of the dorsolateral hook. The discovery of these species increases the number of Metrichia species in the Brazilian Cerrado from seven to eight and are only the eleventh and twelfth caddisfly species reported for Tocantins State.